Familiar barriers still unresolved: a perspective on the Zika virus outbreak research response - Koopmans, Maria Petronella Gerarda; Jänisch, Thomas; Rosenberger, Kerstin; Morales, Ivonne (The lancet. Infectious diseases, 2019)
Summary Research is an important component of an effective response to the increasing frequency of widespread infectious disease outbreaks. In turn, the ability to do such studies relies on willingness of partners in different regions to collaborate and the capacity to mount a rapid research response. The EU-funded ZIKAlliance Consortium has initiated a multicountry epidemiological, clinical, and laboratory research agenda to determine the incidence, risk factors, and outcomes of Zika virus infection in pregnant women and their children. We reviewed the timeline of patient cohort initiation in relation to the Zika virus epidemic and mapped key events regarding funding, regulatory approvals, and site preparation during this timeline. We then assessed barriers and delays that the international research team experienced through a systematic telephone interview. We have identified three major bottlenecks in the implementation of a swift response: the absence of a timeline for the funding process, delays in regulatory and ethical approval, and the challenging logistics of laboratory support, including diagnostics. These bottlenecks illustrate the clear and urgent need for implementing a strong and permanent global emerging infectious diseases research capacity that has structured funding, enables long-term partnerships, and develops basic clinical and laboratorial research and a response infrastructure that is ready to deploy.